(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
Fungi associated with leaves of Senna alata (L.) Roxb. (Cassia alata L.) and their pathogenic potentiality have been discussed. A total of 8 species of fungi belonging to 8 genera of Deuteromycetes were found to be associated with S. alata. The fungi were Acromoniella sp., Arthrinium saccharicola Stevenson, Aspergillus niger Van Tiegh, Cladosporium cladosporioides (Fresen.) de Vries, Colletotrichum gloeosporioides (Penz.) Sacc., Curvularia lunata (Wakker) Boedijn, Nigrospora sphaerica (Sacc.) Mason, Pestalotiopsis guepinii (Desm.) Stay and unidentified Hyphomycetes, C. gloeosporioides and P. guepinii were found to be pathogenic to S. alata. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17568 Journal of Bangladesh Academy of Scnces, Vol. 37, No. 2, 249-252, 2013